ICT adoption on cultural preservation amongst Indian youth in Selangor, Malaysia - Ooslappan, Thuraiveloo; Gill, Sarjit S.; Kunasekaran, Puvaneswaran; Fang, Yi Xue (Human Resource Management Academic Research Society, 2022)
This paper presents the significant role of Information and Communication Technology (ICT) on cultural preservation among Indian Youth in Selangor, Malaysia. A middle-class youth group aged 18 to 35 years old participated in the study in Subang Jaya, Selangor. In-depth interviews, which were used as a qualitative data collection method, helped the researchers in developing a comprehensive understanding of how ICT is used to preserve culture. Usage of multiple and variety of ICT devices in daily life gave the space and opportunity to know about culture. However, some informants feel that socialization and parents imparting knowledge about culture still play an important role. It is hoped that the findings of this study will contribute to the existing literature on how ICT can play a role in preserving culture in the future and among the coming younger generation who will be leaving life in a world surrounded by ICT. Despite being a minority in Malaysia, the Indian community should be given equal rights and access to ICT to carry out their daily functions, including developing their cultural capital and cultural preservation